Does Inflation Targeting Matter? - Sheridan, Niamh (IMF Working Papers; Working Paper ;, 2003)
This paper asks whether inflation targeting improves economic performance, as measured by the behavior of inflation, output, and interest rates. We compare 7 OECD countries that adopted inflation targeting in the early 1990s to 13 that did not. After the early 1990s, performance improved along many dimensions for both targeting and nontargeting countries. In some cases, the targeters improved by more. However, these differences are explained by the fact that targeters performed worse than nontargeters before the early 1990s, and there is regression towards the mean. Once one controls for this, there is no evidence that inflation targeting improves performance.